INFLUENCE OF SHARIA MARKETING CHARACTERISTICS ON CUSTOMERS' SAVING INTEREST AT INDONESIAN SHARIA BANK MAKASSAR BRANCH - Semaun, Syahriyah; Rasyid, Siti; Musmulyadi, Musmulyadi (Jurnal Riset Bisnis dan Manajemen, 2023)
The study aims to measure, investigate, and examine how Islamic This study aims to determine the influence of the characteristics of Sharia Marketing which consists of Theistic (Rabbaniyyah), Ethical (Akhlaqiyyah), Realistic (Al-Waqi'yyah) and Humanistic (Al-Insaniyyah) variables on the interest in saving and to find out the dominant variable that simultaneously influences the characteristics of Sharia Marketing on the interest in saving. This is a quantitative research with descriptive method. The data collection by distributing questionnaires. The methods used to test the hypothesis is Multiple Regression Analysis. The results are: (1)the variable Theistic (Rabbaniyyah), Ethical (Akhlaqiyyah), and Realistic (Al-Waqi'yyah) has a positive and insignificant influence on the variable of interest in saving, (2)the variable Humanistic (Al-Insaniyyah) has a positive and significant influence on the variable of interest in saving and the variable Humanistic (Al-Insaniyyah) has the most dominant influence simultaneously on interest in saving. That influence can be interpreted by increasing customer interest in saving at Bank Syariah Indonesia.